Structural Analysis of How Podocytes Detach from the Glomerular Basement Membrane Under Hypertrophic Stress - Kriz, Wilhelm; Hähnel, Brunhilde; Hosser, Hiltraud; Rösener, Sigrid; Waldherr, Rüdiger (Frontiers in Endocrinology, 2014)
Podocytes are lost by detachment from the GBM as viable cells; details are largely unknown. We studied this process in the rat after growth stimulation with FGF-2. Endothelial and mesangial cells responded by hyperplasia, podocytes underwent hypertrophy, but, in the long run, developed various changes that could either be interpreted showing progressing stages in detachment from the GBM or stages leading to a tighter attachment by foot process effacement (FPE). This occurred in microdomains within the same podocyte; thus features of detachment and of reinforced attachment may simultaneously be found in the same podocyte. (1) Initially, hypertrophied podocytes underwent cell body attenuation and formed large pseudocysts, i.e. expansions of the subpodocyte space. (2) Podocytes entered the process of FPE starting with the retraction of foot processes and the replacement of the slit diaphragm by occluding junctions thereby sealing the filtration slits. Successful completion of this process led to broad attachments of podocyte cell bodies to the GBM. (3) Failure of sealing the slits led to gaps of varying width between retracting foot processes facilitating the outflow of the filtrate from the GBM. (4) Since those gaps are frequently overarched by broadened primary processes the drainage of the filtrate into the Bowman's space may be hindered leading to the formation of small pseudocysts associated with bare areas of GBM. (5) The merging of pseudocysts created a system of communicating chambers through which the filtrate has to pass to reach Bowman's space. Multiple flow resistances in series likely generated an expansile force on podocytes contributing to detachment. (6) Such a situation appears to proceed to complete disconnection generally of a group of podocytes owing to the junctional connections between them. (7) Since such groups of detaching podocytes generally make contact to parietal cells, they start the formation of tuft adhesions to Bowman's capsule.